Computational characterization of isomeric C4H2O systems: Thermochemistry, vibrational frequencies, and optical spectra for butatrienone, ethynyl ketene, butadiynol, and triafulvenone - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (WILEY, 2016)
Species of empirical formula C4H2O have been invoked either as elusive intermediates in flames or oxidations on heterogeneous catalysts, or as long-lived species in the interstellar medium. Butatrienone has been characterized experimentally, but isomers ethynyl ketene, butadiynol, and trifulvenone have been described only by computational modeling. Triafulvenone is of special interest as the ketene analog of the carbonyl compound cyclopropenone; both species contain seriously strained three-membered rings. In contrast to cyclopropenone, which is detected in the interstellar medium, triafulvenone continues to elude experimental capture. The contrast is attributed to a degree of aromatic stabilization in cyclopropenone and anti-aromatic destabilization in triafulvenone. In this report, we characterize the structure, vibrational and electronic spectra, and thermochemistry for triafulvenone and three of its isomers, butatrienone, ethynyl ketene, and butadiynol to assist experimental detection of these elusive species. Our calculations have shown that triafulvenone is the least stable of these four isomers; even the well-known butatrienone, is not the most stable. The so far undetected ethynyl ketene is thermodynamically the most stable of these isomers. To facilitate experimental detection of these species we provide vibrational frequencies calculated using both B3LYP/cc-pVTZ and MP2/cc-pVTZ level model chemistry corrected for anharmonicity including the possibility that the spectra may include overtones and combination bands for these species The regions of intense IR absorption and most important frequencies are also underlined for all the species involved. To guide the search for short-lived C4H2O species, we also characterize the optical spectrum. (c) 2015 Wiley Periodicals, Inc.
Keywords: triafulvalenone; anharmonicity; aceteyleneketene; vibrational spectra; optical spectra; SET MODEL CHEMISTRY; EXCITED-STATE; ALKYNYL; CYCLOPROPENONE; GAUSSIAN-2; GENERATION; PYROLYSIS; MOLECULES